TOPOGRAPHIC CONTROL ON GROUNDWATER FLOW IN CENTRAL OF HARD WATER AREA, WEST PROGO HILLS, INDONESIA - T. Listyani R.A; Nana Sulaksana; Boy Yoseph CSSSA; Adjat Sudradjat (GEOMATE Journal, 2019)
West Progo Hills is one of some hard water area in Indonesia. It doesn’t belong to the groundwater basin because it is difficult to get groundwater. Groundwater can be found in some places with a random point. Dug wells are usually found in the narrow area, as well as springs. By hydrogeological as well as hydro isotope approaches, this research wants to know about groundwater potential in West Progo Hills especially at the central part of it. The groundwater mapping has been done at Girimulyo - Kaligesing and surrounding area, to get some geologic data, water table measurement, and geomorphological data. The result of the research shows that the groundwater table usually follows the local topography. Groundwater table ranges 0.9 – 8 m below surface, it means shallow groundwater table. Dug wells are only locally found, as well as springs. Some springs often found at break of slope, it means that they’re controlled by topography. Based on the groundwater table from dug wells data, groundwater is conformable to the topographic condition. The relationship between elevation and groundwater table gives the correlation coefficient (r) as much as 99.99%. It means that relief is followed by the groundwater level. It can be concluded that relief has a strong correlation with shallow groundwater in the research area, although the stable isotopic data doesn’t support the altitude effect of it. Groundwater flows from high to low lands, such as the upper slope of hills to valleys.